FORMULATION AND STABILITY EVALUATION OF NATURAL SHOWER GEL CONTAINING PIPER BETLE HYDROSOL AND WHITETEN™ - Elianasari, Elianasari; Agustina, Dina Putri (Indonesian Journal of Cosmetics, 2025)
The growing interest in natural-based personal care products has encouraged the development of innovative cosmetic formulations, including shower gels. This study aimed to formulate and evaluate the physical stability of a shower gel containing Piper betle L. leaf hydrosol and WhiteTen™, a botanical-derived brightening complex. The product was prepared through a four-phase process using ingredients such as Sodium Laureth Sulfate, Cocamidopropyl Betaine, PEG-40 Hydrogenated Castor Oil, Menthol, and preservatives, with the pH adjusted to 5.5–6.5. The formulation was evaluated for its organoleptic properties, pH, viscosity, spreadability, rinseability, foam height, and stability under accelerated storage conditions using six temperature cycling periods. The results showed that the shower gel demonstrated stable physical characteristics, including suitable viscosity, good foaming capacity (60 - 80 mm), ease of rinsing (10 seconds), and consistent pH values across different storage temperatures. The incorporation of WhiteTen™ contributed to the product’s brightening potential, enhancing its value as a multifunctional cosmetic. No significant changes were observed in physical appearance or performance after stability testing, indicating that the formulation is stable and suitable for further development as a safe, natural, and functional skincare product.